1975
DOI: 10.1071/ar9750437
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of semiarid grasses. II.* The pattern of root growth in relation to external phosphorus concentration

Abstract: The effect of the external phosphorus concentration on the pattern of root development in mulga, Mitchell and buffel grasses was examined. During seedling and early vegetative growth, the pattern of root growth suggested that the emergence of axes, their extension and branching were coordinated in such a way that the mean rate of extension and distance between branches remained fairly constant for each component of the root system. Phosphorus deficiency did not greatly affect the length of the seminal axis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 10 publications
2
16
0
3
Order By: Relevance
“…The high SRL of eight grasses with low nutrient supply was reported previously (Fitter 1985). Christie and Moorby (1975) also observed that the SRL of three grasses was higher in a low P solution (0.003 mg L-I) than in a high P solution (3 mg L-I). In the present study, the same trend was found in the rice genotypes grown in the ammonium-N solution, suggesting an adaptive response to low fertility medium.…”
Section: Discussionmentioning
confidence: 59%
“…The high SRL of eight grasses with low nutrient supply was reported previously (Fitter 1985). Christie and Moorby (1975) also observed that the SRL of three grasses was higher in a low P solution (0.003 mg L-I) than in a high P solution (3 mg L-I). In the present study, the same trend was found in the rice genotypes grown in the ammonium-N solution, suggesting an adaptive response to low fertility medium.…”
Section: Discussionmentioning
confidence: 59%
“…1). Christie (1975), showed that greater SRLs are usually due to the production of roots with a smaller diameter, suggesting that exposure to ambient pollution resulted in the production of longer, thinner roots.…”
Section: Resultsmentioning
confidence: 99%
“…Another problem is that thinner roots could be prone to rapid dehydration and loss of turgor pressure, which is essential for the maintenance of cell expansion and root elongation. No direct measurements of root diameter were made although Christie (1975), working on semi arid grasses demonstrated that high root length/weight ratios were generally characteristic of roots with a small diameter. High SRLs could also be due to roots with less densely packed cells or root cells with thinner walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Christie (1975) found that phosphorus deficiency for three grasses decreased the average root diameter to 85% of its value on normal plants. For example, mulga grass root radius was 0.20 mm at 3 mg L -\ phosphorus and 0.17 mm at 0.003 mg L -\ phosphorus.…”
Section: Numbers Of Rootsmentioning
confidence: 98%